Disabled children and the law : research and good practice - Read, Janet, 1947- (Jessica Kingsley Pub., 2006)
Praise for the first edition: 'This book helps readers understand the relevant laws, and to apply these laws confidently and creatively to improve the quality of life for children with disabilities. While research-based and informative, the book is also very readable.' - Community Practitioner. 'This is a first-rate book which sets out to review the main statutes, guidance, research and good practice that relate to disabled children ... essential reading for people who work with disabled children and their families, social policy and law students, as w.